2020
DOI: 10.1136/bmjopen-2020-040999
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning: Promoting Effective and Aligned Communication in the Elderly (ACP-PEACE): the study protocol for a pragmatic stepped-wedge trial of older patients with cancer

Abstract: IntroductionAdvance care planning (ACP) is associated with improved health outcomes for patients with cancer, and its absence is associated with unfavourable outcomes for patients and their caregivers. However, older adults do not complete ACP at expected rates due to patient and clinician barriers. We present the original design, methods and rationale for a trial aimed at improving ACP for older patients with advanced cancer and the modified protocol in response to changes brought by the COVID-19 pandemic.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 82 publications
0
8
0
1
Order By: Relevance
“…Clustered care is a way of providing multiple elements of care in the same setting and, at the same time, is highly operational [16][17][18]. It is not just at the time of PICC placement, but throughout the entire care process after placement, so it needs to be applied with good rules of care, with clear goals and time characteristics [19].…”
Section: Discussionmentioning
confidence: 99%
“…Clustered care is a way of providing multiple elements of care in the same setting and, at the same time, is highly operational [16][17][18]. It is not just at the time of PICC placement, but throughout the entire care process after placement, so it needs to be applied with good rules of care, with clear goals and time characteristics [19].…”
Section: Discussionmentioning
confidence: 99%
“…These studies reported having to collect primary data that were expected to be readily available, including patient-reported outcomes (PROs), previously completed questionnaires, and advance care planning conversations. 16 This led to time- and monetary-consuming adjustments as illustrated by a project using Epic when they said, “We would have appreciated greater ease and flexibility of automatically responding to patient-reported information, including PROs to match participants’ needs. Automatically assigning the intervention to specific patients using Epic EHR logic and based on EHR data was clunky, time consuming, and expensive.…”
Section: Resultsmentioning
confidence: 99%
“…Natural language processing-screened human abstraction represents an efficient and useful approach for measuring EHR outcomes in large pragmatic studies and is increasingly used to measure palliative care outcomes similar to the one we examined. 34,[62][63][64][65] In the 2512-patient PICSI-H Trial 1, measuring the primary outcome using conventional manual abstraction would have required thousands of abstractor-hours, which is both costly and time consuming. In contrast, NLP-screened human abstraction allowed investigators to make up-front investments in developing NLP and collecting training and validation data and then measure the primary outcome during a smaller number of abstractor-hours with acceptable losses in sensitivity and power.…”
Section: Discussionmentioning
confidence: 99%